Effects of Genetic Polymorphism on Susceptibility to Nephrotoxic Properties of BTEXs Compounds. Issue 8 (August 2018) - Neghab, Masoud; Nourozi, Mohamad Amin; Shahtaheri, Seyed Jamaleddin; Mansoori, Yaser; Bazzaz, Javad Tavakkoly; Nedjat, Saharnaz
Abstract : Objective: The aim of this study was to ascertain whether genetic polymorphism affects susceptibility of individuals to nephrotoxic potentials of benzene, toluene, ethyl-benzene, and xylenes (BTEXs). Methods: Fifty BTEXs exposed workers with one or more abnormal parameter of kidney function and 232 referent subjects, with similar exposure history, free from any abnormal kidney parameters were investigated. Atmospheric concentrations of BTEXs were measured. In addition, genetic polymorphisms were determined by multiplex polymerase chain reaction (PCR) and PCR-restriction fragment length polymorphism (RFLP). Results: The frequencies of GSTP1 Ile-Val/Val-Val, null GSTT1, and null GSTT1/GSTM1 genotypes and mean values of blood urea nitrogen and plasma creatinine were significantly higher, while average glomerular filtration rate was significantly lower in cases than in referent subjects. Conclusion: These findings indicate that individuals carrying null GSTT1 or null GSTT1/GSTM1 are more susceptible to nephrotoxic properties of BTEXs compounds.